Acceptability and Content Test of Nastar Cake Modified with Red Bean Flour (Phaseolus Vulgaris L) as A High Protein Food - Siregar, Indah Risky; Salianto, Salianto; Suraya, Rani (Indonesian Journal of Global Health Research, 2024)
Nastar cake is one of the pastries made from wheat flour. Nastar cake is one of the pastries that is small round, shiny surface, made of flour, margarine, refined sugar, egg yolk and filled with pineapple jam. Nastar cake with the addition of red bean flour can be put to good use as a high-protein food. This study aims to determine the effect of adding red bean flour on the test of acceptability (hedonic) and protein content in pineapple cake. This research method uses an experimental method using Complete Randomized Design (RAL), with independent variables, namely formulas with the addition of red bean flour at 0%, 50%, 75%. Variables are tied in the form of color, texture, aroma, and taste of pineapple cake. Hedonic test data was obtained from 25 untrained panelists, namely students of the UINSU Faculty of Public Health. Data analysis for the acceptability test was carried out using the ANOVA method and Duncan's follow-up test. The results of this study found that the acceptability of pineapple cake based on the assessment of color, texture, aroma, and taste that was preferred by panelists was F0 without the addition of red bean flour (control) with an average result of 4.09 (likes), while F1 with an average of 3.23 (less likes), and F2 with an average of 2.78 (dislikes). It is known based on the test results of the highest protein content found in F2 (10.03%), F1 (9.89%), and the lowest F0 (9.72%). As a high-protein food with the addition of red bean flour, it is expected to be an alternative food that is high in protein to prevent stunting.